A CASE STUDY OF GRAMMATICAL ERROR ANALYSIS OF CREATIVE WRITING - Yuliyana Yuliyana; Ahmida Rizki Aulia (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2017)
We realize the difficulty of acquiring skill in second language writing. Many aspects in writing should be concerned, include model texts, grammar, spell-check, punctuation and prepositions. Learners have to study how to convey their understanding of grammatical rules. In this research, researchers conducted analysis in grammatical error based on surface strategy taxonomy. Surface strategy taxonomy highlights the way surface structures are altered. It includes omission, addition, misformation, and misordering errors. There are 125 grammatical errors found in 12 creative writings which include 37 errors in omission, 10 errors in addition, 13 errors in misinformation, 1 errors in misordering, and 64 errors in others category. Researchers mostly found errors in use of tenses and punctuation as other error category. The participant did not make any improvement in his creative writings from March 2013 up to January 2014 because he repeated make same grammatical errors in each article.